IMPLEMENTASI REFORMASI BIROKRASI DI KEPEGAWAIAN DAERAH DALAM PENYELENGGARAAN GOOD GOVERNANCE (STUDI DI BKDD MINAHASA TENGGARA) - Taha, Ramadhan Hi. Zaini Dg (Universitas Sam Ratulangi, 2013)
Bureaucratic reform is basically an effort to reform and fundamental changes to the system of governance, especially concerning institutional aspects (organization), management (business process) and human resources. Various problems / barriers that lead to the system of governance is not running or is not expected to run properly must be reorganized or updated. Bureaucratic reform was implemented in order to realize good governance (good governance). In other words, reform is a strategic move to build the state apparatus in order to be more efficient and effective in carrying out general governance and national development. Therefore, the government must have a concept or new idea in the bureaucracy of policy instruments, as a systemic choice. According to the shape and spatial implementation that have long-term consequences are carefully considering the interests of central and local government, especially the more priority to the public interest for good governance. Keywords: Reforms, local employment, good governance.